2022
DOI: 10.1111/geb.13532
|View full text |Cite
|
Sign up to set email alerts
|

Availability and proximity of natural habitat influence cropland biodiversity in forest biomes globally

Abstract: Aim: Agriculture is one of the greatest pressures on biodiversity. Regional studies have shown that the presence of natural habitat and landscape heterogeneity are beneficial for biodiversity in agriculture, but it remains unclear whether their importance varies geographically. Here, we use local biodiversity data to determine which local and landscape variables are most associated with biodiversity patterns and whether their association varies between tropical and non-tropical regions.Location: Global terrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
8
1
Order By: Relevance
“…Previous research has shown the importance of natural habitat in buffering the effects of human activity on biodiversity (Macchi et al 2020;Outhwaite et al 2022) but our results suggest nuanced effects depending on crop. In landscapes with wheat cultivation, areas with higher percentage of natural habitat experience steeper decreases in species richness and abundance with yield, likely from higher initial biodiversity as natural habitat is positively related to species richness and abundance in wheat landscapes (Table S20).…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Previous research has shown the importance of natural habitat in buffering the effects of human activity on biodiversity (Macchi et al 2020;Outhwaite et al 2022) but our results suggest nuanced effects depending on crop. In landscapes with wheat cultivation, areas with higher percentage of natural habitat experience steeper decreases in species richness and abundance with yield, likely from higher initial biodiversity as natural habitat is positively related to species richness and abundance in wheat landscapes (Table S20).…”
Section: Discussioncontrasting
confidence: 68%
“…However, primary vegetation in modi ed landscapes likely represents an important source of biodiversity and ecosystem services for the surrounding farmland (Karp et al 2013;Outhwaite et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations